2015
DOI: 10.2306/scienceasia1513-1874.2015.41.170
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex PCR assay for rapid and simultaneous detection of rubber tree pathogens Phytophthora spp. and P. palmivora

Abstract: Phytophthora spp. cause devastating effects on crops and natural ecosystems worldwide. In Thailand, P. palmivora is an important pathogenic species of the rubber plant (Hevea brasiliensis), reducing latex production. This study aimed to develop a PCR-based method to rapidly and simultaneously detect the genus Phytophthora and P. palmivora. A single round nested multiplex PCR with 4 primers, Phy1s/Phy2a/Pal1s/Pal2a, and a single round seminested multiplex PCR using 3 primers, Phy1s/Phy2a/Pal2a, were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…It proved that 13 collected isolates from rotting pods of 8 surveyed locations were P. Palmivora, the causal agent of black pod diseases on cocoa. The previous research of Chirapongsatonkul et al (2015) also found that molecular identification of P. palmivora isolates with PCR method using specific primers of Pal1s and Pal2a could amplify the target DNA at 650 bp.…”
Section: Molecular Identificationmentioning
confidence: 92%
See 1 more Smart Citation
“…It proved that 13 collected isolates from rotting pods of 8 surveyed locations were P. Palmivora, the causal agent of black pod diseases on cocoa. The previous research of Chirapongsatonkul et al (2015) also found that molecular identification of P. palmivora isolates with PCR method using specific primers of Pal1s and Pal2a could amplify the target DNA at 650 bp.…”
Section: Molecular Identificationmentioning
confidence: 92%
“…Molecular identification was aimed to ensure that the obtained isolate was P. palmivora. This analysis was conducted using PCR method with specific primers for P. palmivora (pal1s and pal2a) with target size of 650 bp (Chirapongsatonkul et al, 2015). DNA extraction of P. palmivora isolates was performed using CTAB method (Subandiyah, 2003).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…juga ditemukan dari hasil isolasi pada bagian ranting muda atau dekat dengan tunas yang gejalanya hampir sama dengan di tangkai daun dan ibu tulang daun yaitu bercak coklat kehitaman (Gambar 3c). Menurut Soepadmo ( 1 9 7 8 ) dan Chirapongsatonkul et al (2015) gejala penyakit gugur daun Phytophthora yaitu terdapat bercak coklat tua atau hitam pada tangkai daun dengan bintik putih di tengahnya yang merupakan lateks membeku. Pada umumnya bercak terdapat pada bagian pangkal tangkai daun dan kadang-kadang terdapat di ibu tulang daun maupun di ranting.…”
Section: Pengamatan Makroskopis Dan Mikroskopis Dari Gejala Seranganunclassified
“…Aside from P. palmivora, which is considered as the major Phytophthora pathogen of plantation crops, there are many other species of Phytophthora, which are known to attack these crops as reported worldwide (Chirapongsatonkul et al, 2015;Surujdeo-Maharaj, 2016). However, the ambiguity on the identity at the species level of Phytophthora in the Philippines is still a challenge as few studies have been made especially on molecular characterization.…”
mentioning
confidence: 99%